Human Resource Competency Development and Work Productivity: The Mediating Role of Knowledge Management at The Palm Oil Research Center, Medan - Dinda Syahfitri Ramadhani; Rahmi Syahriza; Faisal Umardani Hasibuan (Universitas Islam Darul 'ulum Lamongan, 2026)
This study examines the effect of human resource competency development on work productivity and tests the mediating role of knowledge management at the Palm Oil Research Center (PPKS) Medan. A quantitative, cross-sectional survey was conducted using 60 purposively selected employees and researchers who were involved in competency-development, research, and knowledge-sharing activities. Data were collected through a five-point Likert questionnaire and analyzed in IBM SPSS using item validity tests, Cronbach’s alpha, classical-assumption tests, regression-based path analysis, and the Sobel test. Human resource competency development had a strong positive effect on knowledge management (B = 0.568, β = 0.709, p < 0.001) and a positive direct effect on work productivity (B = 0.545, β = 0.461, p = 0.001). Knowledge management also positively affected work productivity (B = 0.465, β = 0.315, p = 0.019). The first model explained 50.3% of the variance in knowledge management, whereas the second model explained 51.7% of the variance in work productivity. Recalculation of the indirect effect using the mediator-to-outcome coefficient produced a Sobel statistic of 2.299 (p = 0.022), indicating partial mediation. The findings demonstrate that competency development produces stronger productivity gains when employee knowledge is systematically created, documented, shared, and applied. PPKS Medan should therefore integrate competency mapping, continuous learning, mentoring, communities of practice, and a searchable institutional knowledge repository within a unified human-resource and knowledge-management strategy.